Remarks on number theory over additive arithmetical semigroups - Indlekofer, K.-H.; Kaya, E. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 511We deal with additive arithmetical semigroups and present old and new proofs for the distribution of zeros of the corresponding $ζ$-functions. We use these results to prove prime number theorems and a Selberg formula for such semigroups.